2014
DOI: 10.14402/jkamprs.2014.36.6.253
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial Trauma Trends at a Tertiary Care Hospital: A Retrospective Study

Abstract: Purpose:Maxillofacial fractures are rapidly increasing from car accidents, industrial accidents, teenaged criminal activity, and sports injuries. Accurate assessment, appropriate diagnosis, and preparing individual treatment plans are necessary to reduce surgical complications. We investigated recent trends of facial bone fracture by period, cause, and type, with the objective of reducing surgical complications.Methods:To investigate time trends of maxillofacial fractures, we reviewed medical records from 2,19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 25 publications
(33 reference statements)
0
24
2
1
Order By: Relevance
“…There was no significant difference in the number of patients over the 4 years studied from 2010 to 2013. In contrast, Jeon et al 11 reported that the number of fractures approximately doubled each trimester in their analysis on facial trauma trends during 3 periods between 1981 and 2012. Kim et al 2 reported an increase in the number of fractures over time.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…There was no significant difference in the number of patients over the 4 years studied from 2010 to 2013. In contrast, Jeon et al 11 reported that the number of fractures approximately doubled each trimester in their analysis on facial trauma trends during 3 periods between 1981 and 2012. Kim et al 2 reported an increase in the number of fractures over time.…”
Section: Discussionmentioning
confidence: 91%
“…In particular, Al Ahmed et al 10 reported a huge bias against men with an 11:1 ratio, which may be due to ethnic characteristics in the UAE where social freedom for women is more restrictive than in other countries. On the other hand, in countries with more social freedom for women such as Greenland, Finland, and Austria, the sexual ratio remains 2.1:1 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral and maxillofacial trauma may follow MVAs and account for approximately 5% of the hospitalizations caused by trauma . Retrospective studies suggest that MVAs and falls are the main cause of dental trauma, whereas MVAs alone are the main cause of maxillofacial trauma …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Based on epidemiological data, it has been suggested such injuries are most frequently incurred by males in their twenties and thirties. 6,7 Regardless of their intensity and origin, craniofacial injuries rank among the most dangerous, and frequently life-threatening traumas, and often require immediate surgery. This is linked with a significant risk of damage to the vital organs of the body located within the head and neck region, i.e.…”
Section: Introductionmentioning
confidence: 99%